Koleksyen Cherita Bala Nembiak Ari Kampung Sampun Gerunggang : STORIES COLLECTION FROM CHILDREN OF KAMPUNG SAMPUN GERUNGGANG - Athirah, Azhar (UNIMAS Publisher, 2024)
The present generation tends to gravitate towards spending their time on electronic devices, engaging in activities such as browsing social media or playing games, regardless of whether they reside in rural or urban areas. Children who cultivate a habit of reading not only enhance their communication and language skills but also play a pivotal role in mitigating the illiteracy rate among Malaysian children. Access to learning resources and experiences should be extended to all, including those in rural areas.